Embedding perseverative interest of a child with autism in text may result in improved reading comprehension: A pilot study. (3rd May 2016) - El Zein, Farah; Solis, Michael; Lang, Russell; Kim, Min Kyung
Abstract: Objective : We investigated the effects of embedding the perseverative interest (PI) of a child with autism (i.e. cars) within texts on reading comprehension. Methods : A PI text condition (text altered to include cars) was compared with a non-PI text condition (same story without cars inserted) in an alternating treatment design. Dependent variables were responses to reading comprehension questions and number of words uttered during an oral retell (i.e. curriculum-based measures [CBMs]). The reading level, instructional routines, and therapist where held constant across the randomly alternated conditions. Results : Both CBMs suggested that reading comprehension was enhanced when the story included the child's PI. Conclusions : These preliminary findings suggest that embedding the PIs of students with autism spectrum disorder within readings may result in more accurate responses to reading comprehension questions and more detailed oral retelling. These findings are discussed in terms of potential directions for future research.